Solitary median maxillary central incisor and normal stature: a report of three cases - S. Y. CHO, & B. K. DRUMMOND (Paediatric Dentistry, 2006)
Congenital absence of maxillary central incisors is rare [1]. The presence of a solitary median maxillary central incisor (SMMCI) is even rarer.